Umbilical Myiasis in a Newborn: a case report - Dey, PK; Bhattacharya, T; Pal, SN; Das, S; Pal, S (Journal of College of Medical Sciences-Nepal, 2013)
Myiasis is an infection of live mammalian tissue by the larval forms of dipteran flies, usually infects domestic and wild animal but human may be affected sometimes. Although adult cases have been reported, neonatal myiasis is a rare condition. Umbilical myiasis is very rare in newborns with few reported cases in the literature. In this article we are reporting an eight day old female neonate from urban slum area in West Bengal (India) presented with umbilical myiasis and omphalitis. She was infected with Chrysomya spp. larvae, was clinically well. Journal of College of Medical Sciences-Nepal, 2012, Vol-8, No-4, 42-45 DOI: http://dx.doi.org/10.3126/jcmsn.v8i4.8700